2010
DOI: 10.1038/sc.2010.19
|View full text |Cite
|
Sign up to set email alerts
|

Non-assisted treadmill training does not improve motor recovery and body composition in spinal cord-transected mice

Abstract: Study design: Experiments in a mouse model of complete paraplegia. Objectives: To evaluate the effect of non-assisted treadmill training on motor recovery and body composition in completely spinal cord-transected mice. Settings: Laval University Medical Center, Neuroscience Unit, Quebec City, Quebec, Canada. Methods: Following a complete low-thoracic (Th9/10) spinal transection (Tx), mice were divided into two groups that were either untrained or trained with no assistance. Training consisted of placing the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…Only 41% of complete and 63% of incomplete SCI studies reported randomization of animals into groups (Carvalho et al, 2008;Engesser-Cesar et al, 2005Erschbamer et al, 2006;Fischer and Peduzzi, 2007;Fong et al, 2005;Goldshmit et al, 2008;Ichiyama et al, 2009;Kuerzi et al, 2010;Lankhorst et al, 2001;Lee et al, 2010;Liu et al, 2008;Lovely et al, 1986;Maier et al, 2009;Nothias et al, 2005;Park et al, 2010;Singh et al, 2011, Smith et al, 1982Tillakaratne et al, 2010;Ung et al, 2010;Van Meeteren et al, 2003). Blinded outcome measures were undertaken in 29% of complete and 54% of incomplete SCI studies (Carvalho et al, 2008;Engesser-Cesar et al, 2007;Erschbamer et al, 2006;Foret et al, 2010;Fouad et al, 2000;Ichiyama et al, 2009;Kubasak et al, 2008;Kuerzi et al, 2010;Lankhorst et al, 2001;Maier et al, 2009;Multon et al, 2003;Oh et al, 2009;Park et al, 2010;Singh et al, 2011;Smith et al, 2006;Tillakaratne et al, 2010;Timoszyk et al, 2005, Zhang et al, 2007.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Only 41% of complete and 63% of incomplete SCI studies reported randomization of animals into groups (Carvalho et al, 2008;Engesser-Cesar et al, 2005Erschbamer et al, 2006;Fischer and Peduzzi, 2007;Fong et al, 2005;Goldshmit et al, 2008;Ichiyama et al, 2009;Kuerzi et al, 2010;Lankhorst et al, 2001;Lee et al, 2010;Liu et al, 2008;Lovely et al, 1986;Maier et al, 2009;Nothias et al, 2005;Park et al, 2010;Singh et al, 2011, Smith et al, 1982Tillakaratne et al, 2010;Ung et al, 2010;Van Meeteren et al, 2003). Blinded outcome measures were undertaken in 29% of complete and 54% of incomplete SCI studies (Carvalho et al, 2008;Engesser-Cesar et al, 2007;Erschbamer et al, 2006;Foret et al, 2010;Fouad et al, 2000;Ichiyama et al, 2009;Kubasak et al, 2008;Kuerzi et al, 2010;Lankhorst et al, 2001;Maier et al, 2009;Multon et al, 2003;Oh et al, 2009;Park et al, 2010;Singh et al, 2011;Smith et al, 2006;Tillakaratne et al, 2010;Timoszyk et al, 2005, Zhang et al, 2007.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…Blinded outcome measures were undertaken in 29% of complete and 54% of incomplete SCI studies (Carvalho et al, 2008;Engesser-Cesar et al, 2007;Erschbamer et al, 2006;Foret et al, 2010;Fouad et al, 2000;Ichiyama et al, 2009;Kubasak et al, 2008;Kuerzi et al, 2010;Lankhorst et al, 2001;Maier et al, 2009;Multon et al, 2003;Oh et al, 2009;Park et al, 2010;Singh et al, 2011;Smith et al, 2006;Tillakaratne et al, 2010;Timoszyk et al, 2005, Zhang et al, 2007. Histological analysis to confirm the extent of the lesion were performed in 76% of complete, but only 46% of incomplete SCI studies (Barriere et al, 2008;Boyce et al, 2007 Kuerzi et al, 2010;Lankhorst et al, 2001;Lee et al, 2010;Liu et al, 2008;Lovely et al, 1986;Maier et al, 2009;Moshonkina et al, 2002Moshonkina et al, , 2004Multon et al, 2003;Nothias et al, 2005;Park et al, 2010;Petruska et al, 2007;Singh et al, 2011;Smith et al, 1982Smith et al, ,2009Smith et al, ,2006Tillakaratne et al, 2010;Ung et al, 2010;Zhang et al, 2007). The three studies (7%; …”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Fouad et al, 2000, no significant difference in kinematic and locomotor functional tests was observed in rats with incomplete SCI after early treadmill training (Fouad et al, 2000). Similarly, a study by Ung et al, 2010 reported no difference in locomotor function and muscle fiber conversion after treadmill training in complete transection injured mice (Ung et al, 2010).…”
Section: Rehabilitation Interventionsmentioning
confidence: 95%